THE COMPONENT METHOD OF SCENE ANALYSIS AND OBJECT RECOGNITION - Vechur, Aleksander; Chayka, Aleksey; Chemodakov, Yuriy (International Journal of Computing, 2014)
The main aim of this work is to propose method that allows some machine to determine surrounding objects. It is important that algorithm must use small computer resources so that machine could work in real time. To improve segmentation on natural images, it is necessary to combine multiple features effectively. Our experimental results are consistent with the theoretical analysis.